The EFFECT OF HOST EGG STORAGE DURATION OF Corcyra cephalonica AND THE NUMBER OF EGG CARDS ON THE PARASITIZATION OF THE EGG PARASITOID Trichogramma japonicum: PENGARUH LAMA PENYIMPANAN INANG Corcyra cephalonica DAN PERBANDINGAN JUMLAH PIAS TERHADAP PARASITASI PARASITOID Trichogramma japonicum - Kemal Fathirsyam; Ramadhani Mahendra Kusuma; Noni Rahmadhini (Universitas Wahid Hasyim, 2026)
Trichogramma japonicum is an important biological control agent used against Lepidopteran pests, and its mass production success strongly depends on the quality of the host eggs Corcyra cephalonica used for its development. This study aimed to determine the effect of storage duration of host eggs Corcyra cephalonica and the number of egg cards (pias) on the parasitization performance of the egg parasitoid Trichogramma japonicum. The research was conducted at the Parasitoid Laboratory of BBPPTP Surabaya using a completely randomized design (CRD) with two factors: egg storage duration (no storage, 1 week, and 2 weeks) and number of pias (3, 4, and 5). Observed parameters included host egg quality and quantity, parasitization rate, percentage of adult emergence, and sex ratio of the parasitoid. The results showed that egg storage duration significantly affected all observed parameters. Fresh eggs without storage produced the highest quality, with normal egg percentages reaching 97%, while two-week storage significantly reduced egg quality to below 68%. The highest parasitization rate was obtained from the combination without storage and three pias (P1V1), reaching 84.57%, whereas two-week storage reduced parasitization to around 66%. The highest adult emergence (87.83%) also occurred in P1V1, while the lowest was observed in P2V3 (74.29%). Similarly, the highest female proportion was recorded in P1V1 (86.67%), and the lowest in P2V3 (71.33%).